SCANNING ELECTRON MICROSCOPY OF THE RAT ADRENAL GLAND AFTER SURGICAL LASER EXPOSURE - K. G. Kemoklidze; Yu. K. Alexandrov; N. A. Tiumina; D. E. Pukhov (Бюллетень сибирской медицины)
Aim. We studied via low vacuum scanning electron microscopy the effects of a surgical laser exposure to adrenal glands and results of regeneration processes after. Materials and methods.Purpose of this work is modeling of effects of the removal with a surgical laser a pathological focus in the adrenal glands. For this Wistar male rat (n = 19) adrenal glands were researched without the laser exposure, immediately after it and 1 month later. Results. Immediately after exposure occurs laser ablation crater with rough edges and melted surface penetrated by equidistant pores, which are footprints of blood vessels. Beneath of the surface are numerous vaporizationbubbles. Around the crater, the surface wrinkles and sags due to decreased ability to retain water. 1 month after the laser damage, the affected area tightened by a scar. Its coarse bundles of collagen fibers braid shapeless lumps of coal and caverns. Tissues with normal appearance are close to the scar, both outside and inside of the organ. The wrinkling and the sagging are absent. The undamaged organ part has retained the previous shape, without hypertrophies. The damaged part has shrunk. The nature of the regeneration processes indicates a low probability of a relapse after the destruction of a pathological focus via the surgical laser exposure.